High-Fidelity Simulation Scenario: Pyridoxine-Dependent Epilepsy and Treatment - Jacob Anderson; Nathan Arboleda; Vincent Calleo (Association of American Medical Colleges, 2018)
Introduction Treatment of seizures in the neonatal patient is urgent and time sensitive. Effective and timely treatment of this life-threatening condition is vital in preventing mortality and long-term morbidity. This simulation-based curriculum involves the identification and management of a seizure in a 4-day-old neonate with pyridoxine-dependent epilepsy. The target audience is emergency medicine and pediatric residents, pediatric emergency medicine fellows, and medical students. Methods The primary objectives for this simulation are to (1) rapidly initiate stabilization techniques for a seizing neonate, (2) recognize the importance of checking a glucose level in a seizing neonate, (3) demonstrate understanding of antiepileptic medications and dosing, and (4) identify status epilepticus and initiate pyridoxine once initial seizure management has failed. The goals of this simulation are for residents to treat a seizing infant in an emergency department setting, identify status epilepticus, develop a differential diagnosis that includes vitamin B6 deficiency, and correctly administer pyridoxine. Requirements of this simulation include a high-fidelity patient simulator, medical supplies, a patient simulator operator, and one actor. Results This simulation case was performed at the simulation lab at the State University of New York Upstate Medical University with emergency medicine and pediatric residents. Feedback evaluations for the case showed that it improved resident education and clinical skills. Discussion This simulation case was well received and helped residents develop a systematic approach to seizure management of a newborn. Residents reported increased confidence in treating a seizing neonate and increased comprehension of pyridoxine-dependent epilepsy.